2013
DOI: 10.1161/hypertensionaha.113.01511
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prepregnancy Body Mass Index and Their Children’s Blood Pressure and Resting Cardiac Autonomic Balance at Age 5 to 6 Years

Abstract: Adverse intrauterine conditions can program hypertension. Because one of the underlying mechanisms is thought to be cardiac autonomic balance, we investigated the association between prepregnancy body mass index (BMI) and blood pressure and indicators of the autonomic balance in the child at age 5 to 6 years. Also investigated was whether these associations were mediated by standardized birth weight and child BMI. Pregnant women (n=3074) participating in the Amsterdam Born Children and their Development study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 39 publications
(40 reference statements)
5
50
0
1
Order By: Relevance
“…Similarly, higher weight gain early on during the pregnancy, but not later, was associated with an increased risk of an adverse childhood cardio-metabolic risk profile [35] . Another Dutch study among 1,459 mothers and their 5-6-year-old children showed that a higher maternal prepregnancy BMI was associated with higher childhood systolic blood pressure and overall metabolic score, as a measure of a metabolic syndrome-like phenotype, but not with childhood sympathetic drive, parasympathetic drive or heart rate [39,41] . A study among 5,154 motheroffspring pairs from the UK showed that higher maternal pre-pregnancy weight and gestational weight gain in the mid-pregnancy period were associated with higher childhood levels of triglycerides, HDL-cholesterol, apolipoprotein A1 and interleukin (IL)-6 at the age of 9 years [10] .…”
Section: Childhood Outcomesmentioning
confidence: 99%
“…Similarly, higher weight gain early on during the pregnancy, but not later, was associated with an increased risk of an adverse childhood cardio-metabolic risk profile [35] . Another Dutch study among 1,459 mothers and their 5-6-year-old children showed that a higher maternal prepregnancy BMI was associated with higher childhood systolic blood pressure and overall metabolic score, as a measure of a metabolic syndrome-like phenotype, but not with childhood sympathetic drive, parasympathetic drive or heart rate [39,41] . A study among 5,154 motheroffspring pairs from the UK showed that higher maternal pre-pregnancy weight and gestational weight gain in the mid-pregnancy period were associated with higher childhood levels of triglycerides, HDL-cholesterol, apolipoprotein A1 and interleukin (IL)-6 at the age of 9 years [10] .…”
Section: Childhood Outcomesmentioning
confidence: 99%
“…Maternal overweight and obesity are endemic, and there is strong evidence that the next generations are going to bear the brunt in the form of future risk of not only hypertension, but also many other disease conditions. To limit the impact of this epidemic, we need to make inroads into understanding the consequences for the child, particularly the mechanisms driving the increased risk, and provide evidence-based strategies for future interventions; the study of Gademan et al 9 has started down that path. …”
Section: Hypertensionmentioning
confidence: 99%
“…However, as highlighted by Gademan et al 9 in the current issue of Hypertension, maternal obesity in humans is associated with increased risk of being overweight during infancy through to adulthood, and the presence of cardiometabolic disorders such as hypertension. These human data are supported by extensive experimental data in animal models of obesity.…”
mentioning
confidence: 99%
See 2 more Smart Citations